Information and Communication Technologies in Tourism 2014 2013
DOI: 10.1007/978-3-319-03973-2_22
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Role of Facebook in Re-Shaping Backpacker’s Social Interactions

Abstract: The recent Facebook launch of Timeline, Social Graph Search, and the increased use of the mobile Facebook apps has resulted in some important implications for the use of Facebook by backpackers. The purpose of this paper is to (re) explore how Facebook has impacted social relationships between backpackers and their personal, professional, and 'fellow traveller' networks, particularly in-light of these recent changes to Facebook and the increased reduction of anonymity while travelling. An exploratory survey wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…As Urry (2002) emphasised, technology has dramatically shifted corporeal surveillance to digital surveillance, a pervasive disciplinary tool that, for the most part, remains invisible. The invisibility of surveillance and a lack of awareness of risks may explain why it has been found that privacy concerns do not dramatically influence travellers' intentions to share on social media (Parra-Lopez, et al, 2010;Berger & Paris, 2014).…”
Section: Privacy Memory and Ephemeralitymentioning
confidence: 99%
“…As Urry (2002) emphasised, technology has dramatically shifted corporeal surveillance to digital surveillance, a pervasive disciplinary tool that, for the most part, remains invisible. The invisibility of surveillance and a lack of awareness of risks may explain why it has been found that privacy concerns do not dramatically influence travellers' intentions to share on social media (Parra-Lopez, et al, 2010;Berger & Paris, 2014).…”
Section: Privacy Memory and Ephemeralitymentioning
confidence: 99%
“…Most of the studies discussing these issues have dealt with new media and information and communication technologies (ICTs) in general (see Neuhofer & Ladkin, 2017), with no particular focus on the cell phone. There are a number of studies dedicated to specific communication channels like Facebook in the backpacker experience (E. A. Berger & Paris, 2013), but none have been dedicated to the place of the cellular phone or smartphone in this context.…”
Section: The Present Researchmentioning
confidence: 99%
“…As mobile devices are often used for both personal and work related communications, there is the potential for tensions to arise and be exacerbated (Middleton, 2009;Berger & Paris, 2014). These devices are liberating users from the confines of work 'spaces' creating and extending physically antisocial behaviors into home spaces and other non-work environments .…”
Section: Work Communication Tensionsmentioning
confidence: 99%